PERBANDINGAN SHALAT DAN LAKU MANEMBAH ALIRAN KEBATINAN PANGESTU DAN SUMARAH - Widjayanti, Rosmaria Syafariah (Faculty of Ushuluddin and Humanities, 2015)
Adherents of Islam on Java community can be distinguished by the adherents of Islam who are santri orÂ abangan. Muslim santri are adherents of Islam are actually based on the Koran, while the abangan Islam is aÂ follower of Islam that unites the elements of local cultural beliefs and previous pre-Hindu, Hindu IslamicÂ beliefs. Adherents of this syncretic Islam due to the influence and dynamism animissme ancestorâs life andÂ under the influence of Hinduism who entered the archipelago before the arrival of Islam.